Analisis Terhadap Pengabulan Izin Poligami dengan Alasan Telah Menghamili Calon Istri Kedua (Telaah Putusan Nomor 41/Pdt.G/2019/PA.Rtg) - Alfian Arbie; Milhan Milhan (UNES Law Review, 2023)
It turns out that applications for permits for polygamy in Indonesia have various reasons for submission, applications that are very diverse not only include the three reasons stated in the legislation, namely the wife cannot carry out her obligations, has a physical disability and cannot give birth to offspring. In this research, the author found a decision regarding a polygamy permit case on the grounds that the future second wife was pregnant, whose decision was actually granted, namely the decision of the Ruteng Religious Court in Case Number.41/Pdt.G/2019/PA.Rtg. The problems observed in this research relate to the judge's basic considerations in granting permission for polygamy and the review of issues regarding the decision of the Ruteng Religious Court Number.41/Pdt.G/2019/PA.Rtg. This research is a type of library research and qualitative form. Article 57 of the Compilation of Islamic Law and the Marriage Law, impregnating a prospective second wife does not include the permissibility of polygamy. Thu all conditions outside the legislation must of course be adjusted to the conditions. So the panel of judges was guided by Article 43 of Government Regulation number 9 of 1975 that "if the court is of the opinion that there are sufficient reasons for the applicant to have more than one wife, then the court will give its decision in the form of permission to have more than one wife." If we look at maslahah murrasa, it is already known that one of the requirements of maslahah murrasa itself is for the public benefit, not for personal benefit, so that it will bring benefits to humanity and prevent harm to the public, not to reject personal harm or bring benefit. for himself. So according to the author, granting permission for polygamy on the grounds that he has already impregnated the prospective second wife cannot be justified.